Strategic planning of socio-economic development of a large city - T. Frolova (Правоприменение, 2017)
The subject. The article shows the approaches to the process of creating and realizing strategiesof socio-economic development of the largest cities in the Russian Federation. Thestrategies of socio-economic development of the largest cities have been fundamental inthe formation of such city agglomerations as “Big Volgograd” (Volgograd), “Big Rostov”(Rostov), Zhigulevskaya agglomeration (Samara), Nizhegorodskaya agglomeration (NizhnyNovgorod), Chelyabinsk city agglomeration (Chelyabinsk) and these strategies contain themain ways of development which go far beyond the competence of local importance.The purpose. The article addresses the problems that arise in the process of creating strategiesof socio-economic development of the largest cities including the extent of powerbetween public authorities of different levels.The methodology. The systematic approach, methods of formal and comparative analysisof law as well as synthesis are used in the article.Results. Before the adoption of Federal Law “On the Strategic Planning in the Russian Federation”(further down the article 172-FZ) strategic planning was unsystematic and therewere no unitary law-based approaches towards the drafting process of strategic planningdocuments. After the adoption of 172-FZ the situation has not dramatically changed.The analysis of strategic planning in the largest cities shows the lack of unitary approachestowards the drafting process of strategic planning documents, the definitions of missionand strategic goals of development, the assessment of largest cities importance in the contextof over-regional, regional and internal city area development. Also, the peculiarities ofterritorial planning and budgetary process in municipal establishments are not taken intoconsideration.